Operationalizing a patient engagement plan for health research: Sharing a codesigned planning template from a national clinical trial. (24th December 2021) - Etchegary, Holly; Pike, Andrea; Patey, Andrea M.; Gionet, Erin; Johnston, Brian; Goold, Susan; Francis, Vanessa; Grimshaw, Jeremy; Hall, Amanda; ,
Abstract: Introduction: Engaging with patients about their lived experience of health and illness and their experience within the healthcare system can help inform the provision of care, health policies and health research. In the context of health research, however, operationalizing the levels of patient engagement is not straightforward. We suggest that a key challenge to the routine inclusion of patients as partners in health research is a lack of tangible guidance regarding how this can be accomplished. Methods: In this article, we provide guidance on how to codesign and operationalize a concrete patient engagement plan for any health research project. Results: We illustrate a seven‐step approach using the example of a national clinical trial in Canada and provide a patient engagement planning template for use in any health research project. Conclusion: Such concrete guidance should improve the design and reporting of patient engagement in health research. Patient or Public Contribution: The De‐Implementing Wisely Research group is informed by a national 9‐member patient partner council (PPC). The research team includes three lead patient partners who are coinvestigators on the grant that funds the program of research. Members of the council advise on all aspects of the study design and implementation. The ideas presented in this paper were informed by regular communication and planning with the PPC; specific contributions of lead patient partner authors are outlined as follows: Brian Johnston, Susan Goold and Vanessa Francis are patient partners with a wide breadth of experience in the healthcare system and health research projects. The guidance in this article draws on their lived and professional expertise. All patient partner authors contributed to the planning of the manuscript, participated in meetings to develop content and provided critical manuscript edits and comments on drafts.